THE EFFECT OF CIGARETTE SMOKE ON MUCOCILIARY TRANSPORT IN ALLERGIC RHINITIS PATIENTS AT PHC SURABAYA HOSPITAL - Viola Gloria Legestino; Irene Lingkan Parengkuan; Wiyono Hadi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Tobacco is one of the biggest public health threats in the world. According to the World Health Organization (WHO), the use of cigarettes causes the death of ± 8 million people per year worldwide. About 1.2 million are passive smokers who are exposed to cigarette smoke. Mucociliary transport is the first line in the defense mechanism of the nose that works actively to keep the respiratory tract always clean. Exposure to cigarette smoke can increase mucus secretion. Ciliary movement can also be obstructed, thereby interfering with nasal mucociliary transport. Inflammation of the nasal mucosa due to Allergic Rhinitis will obstruct the nose, which can interfere with the work of mucociliary transport.Objective: This study aims to analyze the effect of cigarette smoke on mucociliary transport in Allergic Rhinitis patients.Methods: This research is an observational study using a cross-sectional research method that was carried out at PHC Surabaya Hospital.Results: 20 RA patients were divided into two groups: ten smokers and ten non-smokers. The saccharin test measured mucociliary transport time. The mucociliary transport time for smokers was 8.72 minutes and 4.82 minutes for non-smokers. The results of the Mann-Whitney test obtained a significance value of p = 0.019 < α = 0.05.Conclusions: There is a significant difference in mucociliary transport time between smoking RA patients, where the mucociliary transport time of smoking patients is longer than that of non-smokers.